Fur-rubbing with Piper leaves in the San Martín titi monkey, Callicebus oenanthe - Huashuayo-Llamocca, Rosario (Primate Biol, 2017)
We report observations on fur-rubbing with leaves from Piper aduncum by a San Martín titi monkey, Callicebus oenanthe. Fur-rubbing occurred during the transition from the dry to the rainy season in a titi monkey group living in a forest fragment in the Moyobamba region of Peru. Since Piper leaves include very potent compounds that may affect ectoparasites, we tentatively interpret the observed fur-rubbing as self-medication.